THE STRUGGLE FOR HUMAN RIGHTS IN CAREY’S TRUE HISTORY OF THE KELLY GANG - Fitri Amalia Burhanuddin (Journal of Innovation Research and Knowledge, 2021)
This study aims to find and to describe social problems that focus on the struggle for human rights violations in the novel of True History of the Kelly Gang. The objective of the research is formulated as follows: 1) to reveal the types of human rights violations occur in the novel True History of the Kelly Gang. 2) to know how the main characters struggle to retrieve his human rights.Based on the objectives, the researcher used a qualitative descriptive method in manner. The research focuses on Peter Carey’s True History of The Kelly Gang as a primary source data and the supporting data were collected through sociologicalapproach. The researcher focused on the struggle of main character to retrieve his rights. The result ofthe study showedthat Ned struggled to get his rightsin different way, he do revenge by replying to what the squatter and police had done to Ned. The implication of this study is expected to give information to the reader at literary work and to give helpful reference for other researchers as well as a contribution for the people who are interested in learning sociology of literature especially for the English literature students.